ANALISIS PENENTUAN SUBSEKTOR PRIORITAS PADA BIDANG KELAUTAN INDONESIA (PENDEKATAN DETERMINISTIK INPUT-OUTPUT) - Hubbansyah, Aulia Keiko (Jurnal Visionida, 2018)
The aim of this study is to determine priority subsectors in the field of Indonesian marine. The analysis is done by input-output approach. This study has found several priority subsectors classified into two groups, namely short-term and long-term priority subsector groups. Short-term priority subsectors group in the Indonesian marine sector include fish processing and preservation industries, marine tourism, marine and fisheries support, marine and fisheries education and research services, and fisheries services. Meanwhile, for the long-term priority subsectors group the Indonesian marine sector comprises oil and gas mining and refining, marine trade services, offshore mining, fishery services and shrimp industry. Keywords: Input-Output, Multiplier Effect, Backward Linkages, Forward Linkages